2022
DOI: 10.1007/s00277-022-04816-9
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of the relationship between anemia and iron and zinc deficiencies in children under 5 years of age living in the malaria endemic area of South Kivu/Democratic Republic of Congo

Abstract: The aim of this study was to explore the relationship of iron and zinc deficiencies and anemia in children aged under 5 years living in malaria endemic area of South Kivu/DRC. We conducted a cross-sectional study in the health zone of Miti Murhesa in South Kivu/DRC. A total of 1088 children in good general health were included in this study. Almost 40% of children were anemic. The prevalence of iron deficiency (ID) was found in 34.9% and 49.1% children based on ferritin or free erythrocyte protoporphyrin (FEP)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 45 publications
0
6
1
Order By: Relevance
“…Other studies in South Kivu found lower rates of anemia in non-pregnant women of reproductive age (16.5%) and children aged 6–23 months (47.8–58.6%) compared to our findings [ 9 , 10 , 11 ]. Rates of iron deficiency were lower than rates of anemia, but frequent infections and genetic Hb disorders were mentioned as potential influencers.…”
Section: Discussioncontrasting
confidence: 83%
See 4 more Smart Citations
“…Other studies in South Kivu found lower rates of anemia in non-pregnant women of reproductive age (16.5%) and children aged 6–23 months (47.8–58.6%) compared to our findings [ 9 , 10 , 11 ]. Rates of iron deficiency were lower than rates of anemia, but frequent infections and genetic Hb disorders were mentioned as potential influencers.…”
Section: Discussioncontrasting
confidence: 83%
“…Rates of iron deficiency were lower than rates of anemia, but frequent infections and genetic Hb disorders were mentioned as potential influencers. Determining iron deficiency by free erythrocyte protoporphyrin resulted in higher levels of iron deficiency [ 9 ]. Factors associated with anemia were malnutrition, illness, Plasmodium infection, and zinc and partly iron deficiency, when not measured by serum ferritin [ 9 , 10 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations